1998
DOI: 10.1016/s0895-7061(98)00036-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Spirapril, Isradipine, or Combination in Hypertensive Patients With Left Ventricular Hypertrophy Effects on LVH Regression and Arrhythmogenic Propensity

Abstract: This study was designed to evaluate in 45 hypertensive patients with left ventricular hypertrophy (LVH) the effects of a 6-month course with one of three different antihypertensive regimens (the calcium channel blocker isradipine, the angiotensin converting enzyme inhibitor spirapril in monotherapy, or a combination of the two drugs, n = 15 per group) on blood pressure, LVH regression, and various functional correlates of LVH. All three treatment modalities decreased significantly LV mass index by an average o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
0
9
1
Order By: Relevance
“…Existing evidence demonstrates that optimal blood pressure control and regression of LVH with antihypertensive therapy are associated with improved LV diastolic function, reduced LA size and changes in plasma catecholamines that may contribute to the prevention of cardiac arrhythmias. [62][63][64] Among different classes of antihypertensive agents, angiotensin receptor blockers (ARBs) and angiotensin-converting enzyme inhibitors (ACEIs) appear to have better efficacy in terms of reduction of cardiac arrhythmias. 65 Blockade of RAAS has been proven to regress LVH and likely explains, in part, its protective effect in arrhythmias.…”
Section: Clinical Implicationmentioning
confidence: 99%
“…Existing evidence demonstrates that optimal blood pressure control and regression of LVH with antihypertensive therapy are associated with improved LV diastolic function, reduced LA size and changes in plasma catecholamines that may contribute to the prevention of cardiac arrhythmias. [62][63][64] Among different classes of antihypertensive agents, angiotensin receptor blockers (ARBs) and angiotensin-converting enzyme inhibitors (ACEIs) appear to have better efficacy in terms of reduction of cardiac arrhythmias. 65 Blockade of RAAS has been proven to regress LVH and likely explains, in part, its protective effect in arrhythmias.…”
Section: Clinical Implicationmentioning
confidence: 99%
“…This therapy also lowers the risk of cardiovascular complications (35) and results in fewer episodes of simple or complex arrhythmias (36). Recent reports have demonstrated that an antihypertensive therapy with regression of left ventricular hypertrophy results in a decrease of atrial diameter.…”
Section: Regression Of Left Ventricular Hypertrophy and Reduction Of mentioning
confidence: 99%
“…However, it should also be noted that not only the regression of left ventricular muscle mass, but also the effects of the blood pressure itself cause a reduction in paroxysmal atrial fibrillation. Antihypertensive therapy should lead to a better control of arterial hypertension (35) and consecutively to a regression of left ventricular hypertrophy (36) as well as an improved coronary flow reserve (14). These effects in turn cause an improvement of (8) and a decrease of left atrial dimension (15).…”
Section: Regression Of Left Ventricular Hypertrophy and Reduction Of mentioning
confidence: 99%
“…In pressure overload of the left ventricle, we know that effective treatment of hypertension or critical aortic stenosis is associated with a change in left ventricular morphology and a decrease in left ventricular mass. 10,11 The degree of regression of left ventricular mass is not uniform in these populations. It is possible that there is variability in the regression of trabeculations in pregnancy similar to the variation in the reduction of left ventricular mass in effectively treated pressure-overload states.…”
Section: Article See P 475mentioning
confidence: 94%